Democratic decay and authoritarian resurgence - Lindstaedt, Natasha (Bristol University Press, 2021)
This book introduces students to the concept and causes of democratic decay in the modern world. Illustrating the integral link between public commitment to democratic norms and the maintenance of healthy democracies, it examines the key factors in decaying democracies, including: • Economic inequality; • Corruption; • Populist and authoritarian discourse; • Declining belief in political institutions and processes. Drawing on real-world developments, and including international case studies, the book outlines the extent to which there is a 'democratic recession' in contemporary politics and shows how transnational networks and technology are impacting on this development.